Total Mercury and Methylmercury Concentration in Fish and Their Reduction through Processing - Hajeb, Parvaneh (2009)
This research has been conducted to study the levels of total mercury and methylmercury, and their correlation in different marine fish species available for consumption in Peninsular Malaysia. Artificial methods have been used to remove mercury from fish. Method for methylmercury determination in fish samples was optimized using response surface methodology (RSM). Total mercury and methylmercury levels were determined using Cold vapor atomic absorption spectrophotometry (CV-AAS) and Gas chromatography-micro electron capture detector (GC-μECD), respectively. Samples of twelve species of common marine fish consumed by Malaysians were collected from local wholesale market in Malaysia. On the basis of total mercury and methylmercury levels measured in commonly consumed fish, two species, long tail tuna and short-bodied mackerel identified with high mercury contents were sampled from east and west coast of Peninsular Malaysia. Methods for elimination of mercury in raw fish fillet has been developed using acidic solutions containing mercury chelating agents. The optimum conditions for methylmercury extraction were found by using acid concentration of 12.118 M, cysteine concentration of 2.375%, solvent volume of 1.5 ml, and extraction time of 35 min. Total mercury and methylmercury levels in fish samples studied were in the range of not detected to 1.010 and not detected to 0.914 μg/g wet wt, respectively. The methylmercury to total mercury ratio ranged from 49.1% to 87.5%, with the highest ratio was in predatory fishes. All of the fish species showed strong positive correlation between methylmercury and total mercury levels (R2>0.86). High levels of total mercury and methylmercury were detected in short-bodied mackerel and long tail tuna. Samples of these two species from east coast of Peninsular Malaysia showed higher levels of mercury compared to those from west coast. In all of the locations, significant positive correlations were found between fish body weight and mercury content. The industrial optimized method produced a solution which can remove mercury from raw fish fillet up to 91%. The optimum conditions for mercury reduction was achieved using cysteine concentration of 1.25 %, EDTA of 275 (mg/L), NaCl of 0.5 (%), pH of 3.75 and exposure time of 18 min. The home-used optimized protocol produced a solution which can remove mercury from raw fish fillet up to 81%. The overall optimal condition resulting to the maximum mercury removal in fish fillet was obtained at combined level of pH of 2.79, 0.5% NaCl, and 13.5 (min) of exposure time.